The Influence of Organizational Climate, Compensation and Work Environment on Employee Job Satisfaction - Martini, M.; Triyono, T. (Golden Ratio of Human Resource Management, 2021)
The purpose of this study was to analyze the effect of Organizational Climate, Compensation and Work Environment on Employee Job Satisfaction in Bantaeng District Land Estate. This research was conducted at the Bantaeng District Land Office. The population in this study were all employees at the Bantaeng District Land Office with a total of 37 employees. The sample used in this study is the entire population of 37 people because the total population is below 100. This research is a quantitative descriptive research with a survey method. Data collection was carried out using a questionnaire. Data analysis using descriptive statistics and multiple linear regression.The results of this study indicate that partially or simultaneously the variables Organizational Climate, Compensation and Work Environment have a positive and significant effect on employee job satisfaction at the Bantaeng District Land Office.